2011
DOI: 10.1242/jeb.050583
|View full text |Cite
|
Sign up to set email alerts
|

Flower constancy in honey bee workers (Apis mellifera) depends on ecologically realistic rewards

Abstract: SUMMARYAs first described by Aristotle, honey bee (Apis mellifera) workers show a strong tendency to visit flowers of only one type during a foraging trip. It is known that workers rapidly learn a flower colour when rewarded with artificial nectar (sucrose solution). However, some previous studies report that the degree of constancy after training is unaffected by reward quantity and quality when bees are tested in an array of artificial flowers of two easily distinguished colours, such as blue and yellow. One… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 51 publications
2
71
0
1
Order By: Relevance
“…Presumably, commitment to a single species is adaptive because it eliminates the period of time needed to learn flower handling and nectar extraction when switching to another species (Waser, 1986;Chittka et al, 1999). Honey bees show greater levels of flower constancy in artificial flower arrays when nectar volume, concentration or the number of nectar rewards is increased, providing that these factors are ecologically realistic (Grüter et al, 2011). Another possible explanation for flower constancy is a limited cognitive capacity (Dukas and Real, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Presumably, commitment to a single species is adaptive because it eliminates the period of time needed to learn flower handling and nectar extraction when switching to another species (Waser, 1986;Chittka et al, 1999). Honey bees show greater levels of flower constancy in artificial flower arrays when nectar volume, concentration or the number of nectar rewards is increased, providing that these factors are ecologically realistic (Grüter et al, 2011). Another possible explanation for flower constancy is a limited cognitive capacity (Dukas and Real, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…That is, if the alternative colors are highly distinct in bee color space. However, a recent study 26 suggests that the reported inability of honeybees to adjust their flower choice according to differences in the rewards experienced was caused by the use of unnaturally large nectar (sucrose solution) rewards per flower (see ref. 27 and 28 for a similar argument).…”
Section: Behavioral Flexibility Within Speciesmentioning
confidence: 99%
“…In other words, the farther a bee must fly to forage, the less available that forage is closer by (Seeley 1994;Seeley 1995). Bees have evolved exceptional sensitivity to measuring relative energetic rewards and to discovering new forage sources in the landscape, so a forager will only dance for the "best" forage sites known at any given time (Schmid-Hempel 1987;Schmid-Hempel and Schmid-Hempel 1987;Seeley 1994;Barron et al 2007;Grüter et al 2011). Therefore, each observed dance has already passed a cost/ benefit analysis and represents that bee's economically smart advice for where the colony should direct foraging efforts.…”
Section: Introductionmentioning
confidence: 99%